2022
DOI: 10.3389/fpsyg.2021.645764
|View full text |Cite
|
Sign up to set email alerts
|

Does Fair Coach Behavior Predict the Quality of Athlete Leadership Among Belgian Volleyball and Basketball Players: The Vital Role of Team Identification and Task Cohesion

Abstract: A vast stream of empirical work has revealed that coach and athlete leadership are important determinants of sport teams’ functioning and performance. Although coaches have a direct impact on individual and team outcomes, they should also strive to stimulate athletes to take up leadership roles in a qualitative manner. Yet, the relation between coach leadership behavior and the extent of high-quality athlete leadership within teams remains underexposed. Based on organizational justice theory and the social ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The results confirmed that the scale could be used as a valuable tool in examining the construct of AJ. Since athletes' perceived fairness toward coaches' decisions and behaviors could build a strong relationship between coaches and athletes [ 6 , 58 , 59 ], future studies could use this tool to extend relevant research by examining the relationships between each dimension and various outcomes, such as quality of relationship between athletes and coaches, team cohesion and commitment, athletes' citizenship behaviors, and individual/team performance. In fact, the body of research on organizational justice has empirically found organizational justice have significant relationships with attitudinal as well as behavioral outcomes [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results confirmed that the scale could be used as a valuable tool in examining the construct of AJ. Since athletes' perceived fairness toward coaches' decisions and behaviors could build a strong relationship between coaches and athletes [ 6 , 58 , 59 ], future studies could use this tool to extend relevant research by examining the relationships between each dimension and various outcomes, such as quality of relationship between athletes and coaches, team cohesion and commitment, athletes' citizenship behaviors, and individual/team performance. In fact, the body of research on organizational justice has empirically found organizational justice have significant relationships with attitudinal as well as behavioral outcomes [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the body of research on organizational justice has empirically found organizational justice have significant relationships with attitudinal as well as behavioral outcomes [ 2 ]. Based on the findings of relevant research regarding the athlete-coach relationship [ [58] , [59] , [60] ], the conceptual framework (as shown in Fig. 2 ) can be developed to describe the relationship between AJ and potential outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies [6][7][8][9] that simply examined the relationships between the perception of fairness toward coaching behaviors and athletes' attitudinal or behavioral outcomes, the current study employed a different approach by incorporating the concept of met-expectation as a way to measure athletes' perceptions of the alignment between their expectations (e.g., their role, playing time, and training within their team) and their experiences regarding coaches' behaviors. According to the met-expectation concept, when organization members' expectations are met, they are likely to have a higher level of satisfaction and commitment.…”
Section: Met-expectationmentioning
confidence: 99%
“…Thus, the quality of the athlete-coach relationship is likely to have a profound impact on a team's performance, either facilitating or hindering their success [3][4][5]. While there are several important factors (i.e., leadership, communication, and support) that contribute to a strong athlete-coach relationship, athletes' perceptions of fairness with respect to coaching behaviors can act as a crucial factor in building and maintaining that relationship [6][7][8][9]. However, the topic of athletes' perceptions of fairness has received limited attention in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, proper coaching practices predict athletes' leadership tendencies within the team. Team identification and task cohesion support these relationships (Backer et al, 2022). Therefore, it is crucial to encourage athlete leadership within the teams (Cotterill et al, 2022).…”
Section: Self-leadership On Physical Health Perception Social Relatio...mentioning
confidence: 99%